Answer:
Explanation:
We can simplify the expression √5 × √12 × √50 as follows:
√5 × √12 × √50 = √(5 × 12 × 50)
To simplify the product under the square root, we can factor the numbers into their prime factors:
5 = 5
12 = 2^2 × 3
50 = 2 × 5^2
Therefore, 5 × 12 × 50 = 2^2 × 3 × 5^3 = 2^2 × 5^3
Substituting this back into the original expression, we get:
√5 × √12 × √50 = √(2^2 × 5^3)
Taking the square root of the product, we can simplify further:
√5 × √12 × √50 = √(2^2) × √(5^3) = 2 × 5√5^2 = 2 × 5 × 5 = 50
Therefore, √5 × √12 × √50 simplifies to 50.